A Plasmodium falciparum ubiquitin-specific protease (PfUSP) is essential for parasite survival and its disruption enhances artemisinin efficacy. Issue 1 (13th January 2023) - Arora, Priya; Narwal, Monika; Thakur, Vandana; Mukhtar, Osama; Malhotra, Pawan; Mohmmed, Asif
Abstract : Proteins associated with ubiquitin–proteasome system (UPS) are potential drug targets in the malaria parasite. The ubiquitination and deubiquitination are key regulatory processes for the functioning of UPS. In this study, we have characterized the biochemical and functional role of a novel ubiquitin-specific protease (USP) domain-containing protein of the human malaria parasite Plasmodium falciparum ( Pf USP). We have shown that the Pf USP is an active deubiquitinase associated with parasite endoplasmic reticulum (ER). Selection linked integration (SLI) method for C-terminal tagging and GlmS -ribozyme mediated inducible knock-down (iKD) of Pf USP was utilized to assess its functional role. Inducible knockdown of Pf USP resulted in a remarkable reduction in parasite growth and multiplication; specifically, Pf USP-iKD disrupted ER morphology and development, blocked the development of healthy schizonts, and hindered proper merozoite development. Pf USP-iKD caused increased ubiquitylation of specific proteins, disrupted organelle homeostasis and reduced parasite survival. Since the mode of action of artemisinin and the artemisinin-resistance are shown to be associated with the proteasome machinery, we analyzed the effect of dihydroartemisinin (DHA) on Pf USP-iKD parasites. Importantly, the Pf USP-knocked-down parasite showed increased sensitivity to dihydroartemisinin (DHA), whereas no change in chloroquine sensitivity was observed, suggesting a role of Pf USP in combating artemisinin-induced cellular stress. Together, the results show that Plasmodium Pf USP is an essential protease for parasite survival, and its inhibition increases the efficacy of artemisinin-based drugs. Therefore, Pf USP can be targeted to develop novel scaffolds for developing new antimalarials to combat artemisinin resistance.